Influence of ionic interactions on the photoinduced Birefringence of poly[1-[4-(3-carboxy-4 hydroxyphenylazo) benzene sulfonamido]-1 2-ethanediyl, sodium salt] films - Ferreira, Quirina; Gomes, Paulo J.; Raposo, Maria; Giacometti, J. A.; Oliveira, Osvaldo N.; Ribeiro, Paulo A. (Amer Scientific Publishers, 2007)
Electrostatic interactions govern most properties of polyelectrolyte films, as in the photoinduced bire-fringence of azo-containing polymers. In this paper we report a systematic investigation of optical storage characteristics of cast and layer-by-layer (LbL) films of poly[1 -[4-(3-carboxy-4 hydroxypheny-lazo) benzene sulfonamido]-1,2-ethanediyl, sodium salt] (PAZO). Birefringence was photoinduced faster in PAZO cast films prepared at high pHs, with the characteristic writing times decreasing almost linearly with the pH in the range between 4 and 9. This was attributed to an increased free volume for the azochromophores with the enhanced electrostatic repulsion in PAZO charged to a greater extent. In contrast, in LbL films of PAZO alternated with poly(allylamine hydrochloride) (PAH), the electrostatic interactions between the oppositely charged polymers hampered photoisomerization and molecular rearrangement, thus leading to a slower writing kinetics for highly charged PAH or PAZO.
Keywords: layer-by-layer film; ionic interactions